Attending [to] Futures Matters of Politics in Design Education, Research, Practice - Mehl, Johanna; Höfler, Carolin (adocs, 2023)
If "design" is the lens through which we glimpse into possible futures, this volume asks: What are the futures we are capable of imagining? As a subject of study, design is enabled and constrained by educational institutions and academic traditions. As a profession it is conditioned by systems of labor. As a creative activity it is shaped by what tools are programmed to do. Authors in this book challenge common ways of knowing, being, and doing in design with regard to the futures they facilitate and interrogate the role, responsibility, and potential of a plurality of design practices in confrontation with social and environmental crises. In this way, this volume does not only ask about designed futures, but also the futures of design: What are the consequences drawn from a critical examination of the histories and politics underlying normative renderings of design? How can we disrupt the perpetuation of biases and reification of social injustices? Self-reflexively engaging their own experiences and work, authors in this volume interrogate design in all its convoluted modalities: as activism, practice, discipline, way of knowing, field of study and set of objects.